Efektivitas Media Audiovisual dan Gambar Berseri dalam Meningkatkan Keterampilan Menulis Cerita Pendek - Anita, Fenny; Suriadiman, Noprieka (GERAM, 2024)
This study aims to evaluate the impact of using audiovisual media and picture series on students' short story writing skills. The study is motivated by the low interest and motivation among students in writing, as well as their difficulties in generating ideas, composing cohesive sentences, and using engaging language. A quasi-experimental approach was employed, involving two experimental groups: one group learned using audiovisual media, while the other used picture series. Data on writing skills were collected through performance tests conducted before and after the treatment. The results showed that students who learned using audiovisual media achieved higher average scores in writing skills compared to those who used picture series. Audiovisual media proved to be more effective in helping students express ideas, structure stories, and use more engaging language. Additionally, the study identified an interaction between the type of learning media and students' initial writing abilities, with audiovisual media showing significant benefits for both high- and low-ability students. These findings highlight the importance of selecting appropriate learning media to enhance students' motivation and writing skills. Teachers are encouraged to utilize audiovisual media as an alternative in teaching short story writing to create a more engaging and effective learning environment.